2022
DOI: 10.1039/d2tc02416k
|View full text |Cite
|
Sign up to set email alerts
|

Achieving redox-responsive organic afterglow materials via a dopant–matrix design strategy

Abstract: When compared to their fluorescence counterparts, stimuli-responsive organic afterglow materials exhibit distinct advantages to function normally even in the presence of strong background fluorescence. However, the types of these afterglow...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…The absence of ambient afterglow in difluoroboron β-diketonate (BF 2 bdk) systems is trivial. 35,39,58,62 Our previous study has demonstrated that a suitable organic matrix (the second component) can assist the population of triplet excited states of luminescent dopants and protect dopants' organic triplets, leading to the emergence of significant ambient afterglow in the two-component system. 54,64 Here, we apply a two-component strategy and emulsion polymerization for the preparation of TADF-type organic afterglow nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The absence of ambient afterglow in difluoroboron β-diketonate (BF 2 bdk) systems is trivial. 35,39,58,62 Our previous study has demonstrated that a suitable organic matrix (the second component) can assist the population of triplet excited states of luminescent dopants and protect dopants' organic triplets, leading to the emergence of significant ambient afterglow in the two-component system. 54,64 Here, we apply a two-component strategy and emulsion polymerization for the preparation of TADF-type organic afterglow nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pioneering studies demonstrated that oxygen, mechanical force, temperature, and light can induce a change in the photophysical properties of room-temperature phosphorescence and organic afterglow materials. The reported studies in recent years exhibited that acid (or base), metal ion, and specific chemicals can also trigger a photophysical change in organic afterglow systems either by rational molecular design or by serendipitous finding. For instance, solid-state crown ethers have been reported to recognize specific ions, leading to afterglow enhancement under ambient conditions . Diels–Alder reaction between phosphorescence emitters and external chemicals has been shown to give a significant afterglow change at room temperature .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24] Therefore, design-ing long-lived room temperature phosphorescence (RTP) materials is challenging. In recent years, many strategies have been developed to promote the effective emission of organic phosphorescence, which includes the following two key points: (1) improvement of the intersystem crossing (ISC) efficiency from the lowest excited singlet state (S 1 ) to the excited triplet (T n ) or from the lowest excited triplet (T 1 ) to the ground state (S 0 ), which can be achieved effectively by enhancing the spin-orbit coupling or by reducing the energy gap between the singlet and triplet states; [25][26][27] (2) inhibition of the nonradiative transition process from the lowest excited triplet state to the ground state as much as possible as the active triplet excitons are often quenched by oxygen, solvent, and high temperature. This is generally achieved by introducing microscopic rigid structures and constructing strong interactions.…”
Section: Introductionmentioning
confidence: 99%